Malignant histiocytosis. Case report - RUIZ, OSCAR (2004)
Fourteen year-old male patient referred from Huancayo who presented one month gastric intolerance, jaundice, fever and a lymph proliferative syndrome. Laboratory tests revealed severe pancytopenia due to phagocytosis. Haematologic and anatomy-pathology diagnosis was human malignant histiocytosis. We present this case due to its low frequency and the emergency character of the disease.